Pengembangan Media Pembelajaran Berbasis Web Dengan Pendekatan Progressive Learning Untuk Meningkatkan Hasil Belajar Siswa Pada Elemen Pemrograman Web Di SMK PGRI 2 Sidoarjo - Mellanda Kurniawati; Rindu Puspita Wibawa (CV. SINAR HOWUHOWU, 2026)
Web programming instruction at SMK PGRI 2 Sidoarjo is still delivered through one way, conventional classroom sessions without a system that sequences mastery of learning materials, causing students to write code before grasping the underlying concepts and making it difficult for teachers to monitor individual progress. This study aimed to build a website based learning medium applying a progressive learning approach for the HTML topic within the Web Programming element, to examine its effect on learning outcomes, and to evaluate the resulting user experience. The medium was built through Research and Development using the ADDIE model, with React on the front end and Supabase on the back end, and was tested on 30 eleventh grade Software Engineering students using a one group pretest-posttest design. Expert validation of the medium, materials, test items, and deep learning lesson plan produced scores of 94.17%, 86.92%, 89.44%, and 94.07% respectively, all in the very valid category. The average score rose from 61.67 (pretest) to 86.67 (posttest); a paired samples t-test returned p < 0.001, and the average N-Gain was 0.658 (moderate). The User Experience Questionnaire showed all six dimensions falling between Above Average and Good. These findings indicate that a website based medium that locks progression until a minimum quiz score is met can meaningfully improve HTML learning outcomes while remaining pleasant to use.